Human IL-22 receptor-targeted small protein antagonist suppress murine DSS-induced colitis - Kuchař, Milan; Sloupenská, Kristýna; Rašková Kafková, Leona; Groza, Yaroslava; Škarda, Jozef; Kosztyu, Petr; Hlavničková, Marie; Mierzwicka, Joanna M; Osička, Radim; Petroková, Hana; Walimbwa, Stephen I; Bharadwaj, Shiv; et al. (Cell communication and signaling, 2024)
BACKGROUND: Human interleukin-22 (IL-22) is known as a "dual function" cytokine that acts as a master regulator to maintain homeostasis, structural integrity of the intestinal epithelial barrier, and shielding against bacterial pathogens. On the other hand, the overexpression of IL-22 is associated with hyper-proliferation and recruitment of pathologic effector cells, leading to tissue damage and chronic inflammation in specific diseases including inflammatory bowel disease (IBD). To study a role of IL-22-mediated signaling axis during intestinal inflammation, we generated a set of small protein blockers of IL-22R1 and verified their inhibitory potential on murine model of colitis. METHODS: We used directed evolution of proteins to identify binders of human IL-22 receptor alpha (IL-22R1), designated as ABR ligands. This approach combines the assembly of a highly complex combinatorial protein library derived from small albumin-binding domain scaffold and selection of promising protein variants using ribosome display followed by large-scale ELISA screening. The binding affinity and specificity of ABR variants were analyzed on transfected HEK293T cells by flow cytometry and LigandTracer. Inhibitory function was further verified by competition ELISA, HEK-Blue IL-22 reporter cells, and murine dextran sulfate sodium (DSS)-induced colitis. RESULTS: We demonstrate that ABR specifically recognizes transgenic IL-22R1 expressed on HEK293T cells and IL-22R1 on TNFα/IFNγ-activated HaCaT cells. Moreover, some ABR binders compete with the IL-22 cytokine and function as IL-22R1 antagonists in HEK-Blue IL22 reporter cells. In a murine model of DSS-induced acute intestinal inflammation, daily intraperitoneal administration of the best IL-22R1 antagonist, ABR167, suppressed the development of clinical and histological markers of colitis including prevention of mucosal inflammation and architecture deterioration. In addition, ABR167 reduces the DSS-induced increase in mRNA transcript levels of inflammatory cytokines such as IL-1β, IL-6, IL-10, and IL-17A. CONCLUSIONS: We developed small anti-human IL-22R1 blockers with antagonistic properties that ascertain a substantial role of IL-22-mediated signaling in the development of intestinal inflammation. The developed ABR blockers can be useful as a molecular clue for further IBD drug development.
Keywords: Animals; Interleukin-22; Protein engineering; Immune suppression; HEK293 Cells; receptory interleukinů; kolitida; lidé; interleukiny; síran dextranu; Mice; Dextran Sulfate; myši; HEK293 buňky; modely nemocí na zvířatech; Receptors, Interleukin; Colitis; Disease Models, Animal; Experimental colitis; Interleukins; Inflammatory bowel disease; zvířata; Mice, Inbred C57BL; interleukin 22; myši inbrední C57BL; Humans